A Monitoring and Reseeding Device for Potato Sower. (August 2020) - Shufeng, Liu; Zhaoqin, Lv; Guangling, Zhang; Hanxiang, Wang
Abstract: To solve the problem of artificial detection and replanting in a potato planter, we provide laser sensor-based seeding detection method. In addition, this paper adopts a method for the detection of seeding by designing a monitoring and reseeding device for a potato sower. We also test the performance of the seeding detection and the automatic filling performance of the device. The device adopts the two pairs of laser correlation sensor and contact-travel switch sensor to detect the leak air scoop seeding location. To achieve precise seeding, the proposed device relies on the step motor to drive the seeding device. The experimental result shows that when the working speed is 2–5 km/h, the original average seeding rate of the seeding machine is 91.35%, the average successful replanting rate of the replanting device is 82.17%, and the comprehensive seeding rate is less than 1.5%. In addition, the total seeding rate is 98.5%. The seeding rate and the seepage rate obviously decreased when the line speed is less than 0.5 m/s. The method for seeding detection proved to be accurate, and the effect of the automatic seeding device is highly apparent. The method not only adapts to different sowing speeds and potato sizes, but also provides a theoretical basis for the intelligent design of a potato planter.